When Freedom of Speech and Neofeudalistic Buzzers Collide: A Note for the Politics of Citizenship - Riko, Riko (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2024)
The term “buzzer” was initially employed in business marketing to promote a product or service by initiating a broader discourse and increasing popularity and sales. However, the function of buzzers has evolved from business to politics, where they are utilized by politicians for political campaigns and maintaining power. This article endeavors to propose a novel concept for contemporary Indonesian political buzzers. The new concept is introduced with the term “Neofeudalistic Buzzers.” The term “Neofeudalistic” is derived from the characteristics of the actions of political buzzers who attack critics of the government and its officials, which resembles the practice of feudalism in the era of precapitalism. This conceptual article has identified that the use of buzzers in Indonesian politics has become a significant propaganda tool. Furthermore, it has been found that government-supporting buzzers are often involved in intimidating government critics. The actions of government-supporting buzzers can discredit freedom of speech and create fear among people who are critical of the government. Theoretically, neofeudalistic buzzers add a new vocabulary to the politics of citizenship studies. Meanwhile, neofeudalistic buzzers can provide practical insights for policymakers and democracy activists to regulate and supervise the activities of political buzzers.